Skopje ima mikroklima… A linguistic and cultural analysis of the onomastic and textual layers of Vlatko Stefanovski’s repertoire - Będkowska-Kopczyk, Agnieszka (Poznańskie Studia Slawistyczne, 2024)
This article examines the linguistic and cultural aspects of the language layer in the works of Macedonian musician Vlatko Stefanovski, created during his time with the band Leb i sol (Bread and Salt) and his solo career. The research material comprises the proper names (the band name, album names, and song titles) and lyrics of recordings released in Serbo-Croatian, Macedonian, and English. Therefore, the factors influencing the choice of a particular language in phonographic publications were first studied. Then, the analysis focuses on references to Macedonian culture in selected proper names and lyrics written in the Macedonian language. This research aims to contribute to a deeper understanding of Vlatko Stefanovski’s musical output and the interplay between language and musical production.